APPLICATION OF THE LINEAR SPRING-DASHPOT MODEL IN THE CFD-DEM SIMULATION OF ALUMINA FLUIDIZATION - Branco Jr, A. M. C.; Mesquita, A. L. A.; Vaz, J. R. P. (Revista de Engenharia Térmica, 2015)
The coupling of the Computational Fluid Dynamics (CFD) to the Discrete Element Method (DEM) to simulate fluidization is computationally demanding. Although the Linear Spring-Dahspot (LSD) model can help to reduce the CFD-DEM simulation runtime due to its simplicity, its applicability is not reasonable for all sorts of problems. The objective of the present work is to show the application of the LSD model to the CFD-DEM simulation of alumina fluidization. The simulations were carried out with the software ANSYS FLUENT 14.5 and divided into two parts: (1) the reproduction with ANSYS FLUENT of simulations from the literature in which the LSD model and a representative particle approach were used. (2) the simulation of alumina fluidization and validation with experimental data. The results of three main sets of parameters were analysed to include different DEM and CFD time steps, drag models, the representation of particles with both uniform size and particle size distribution, etc. The main conclusion of this work is that the LSD model and the CFD-DEM approach can be used to model the actual behaviour of alumina fluidized beds, but the high simulation runtime and the correct setting of the strategies used to control it are still limiting factors which deserve special attention.